Alih Fungsi Hak Atas Tanah Adat Di Kecamatan Ubud, Kabupaten Gianyar - dewa sutaraja (Jurnal Hukum Prasada, 2017)
Abstract Research use the empirical research method to study the problems that is 1) What will be domination of land right of custom Subdistrict of Ubud of Regency Gianyar 2) Cause Factors displace the function of custom land; ground as tourism accomodation in Ubud of Regency Gianyar. Theory which rule of law Theory, Theory of Fiction Theory, collective property or Proprilete Collectief, and Theory kewenangan. Through passing approach: legislation approach, analytic approach and approach of law sociology analysed by using method analyse the assistive interprestasi with the analysis qualitative to data obtained. Pursuant to result analyse got by the following node First; Domination of land right of custom Subdistrict Ubud of generally mastered by Countryside, Gate, and krama countryside. This land;ground its child allotment as agriculture farm later;then turn into the tourism accomodation like restorant, villa / hotel of Maneychanger and place park. Second; Factor making to displace the function of allotment of custom land; ground for example ( 1) economic Factor like custom land;ground made by place is effort restorant, villa / hotel of Maneychanger and place parker.(2) Farm openness in development accommodate tourism. Key word, Logistic averting, Right for Mastery, and Custom Earth